1985
DOI: 10.1111/j.1600-0447.1985.tb02585.x
|View full text |Cite
|
Sign up to set email alerts
|

An open multicentre study of the treatment of florid schizophrenia with remoxipride

Abstract: Remoxipride, a novel substituted benzamide, was given for 4 weeks to 18 florid schizophrenics in an open study. The mental state of the majority improved as measured by the Brief Psychiatric Rating Scale. Remoxipride itself did not appear to cause troublesome extrapyramidal effects. There were no significant adverse effects on the cardiovascular system and no significant abnormalities in laboratory tests. These results suggest that remoxipride has antipsychotic effects, and that this should be tested in contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
1

Year Published

1986
1986
2002
2002

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 8 publications
2
8
1
Order By: Relevance
“…Our results are not in line with theoretical consider ations regarding receptor binding of remoxipride [Ogren et al, 1983] and clinical findings concerning the absence of severe motor impairment [Laursen and Gerlach, 1986;McGreadie et al, 1985]. As our test results are not caused by different baseline levels, deterioration o f'subclinical' fine movements by the benzamide could be assumed, as well as the higher frequency and higher dos age of sedatives in the remoxipride group must be taken into account.…”
Section: Discussioncontrasting
confidence: 54%
“…Our results are not in line with theoretical consider ations regarding receptor binding of remoxipride [Ogren et al, 1983] and clinical findings concerning the absence of severe motor impairment [Laursen and Gerlach, 1986;McGreadie et al, 1985]. As our test results are not caused by different baseline levels, deterioration o f'subclinical' fine movements by the benzamide could be assumed, as well as the higher frequency and higher dos age of sedatives in the remoxipride group must be taken into account.…”
Section: Discussioncontrasting
confidence: 54%
“…Indeed, early clinical trials showed that these drugs induced less extrapyramidal side effects than typical neuroleptics such as haloperidol (Guy et al, 1983;Chouinard and Annable, 1984;Lindstrom et al, 1985;McCreadie et al, 1985;Schwarcz et al, 1985;Patris et al, 1990;Lapierre et al, 1992;Gewirtz et al, 1994). However, receptor binding studies revealed that these atypical neuroleptics also have a significant affinity for a receptors (Largent et al, 1988).…”
Section: Introductionmentioning
confidence: 93%
“…69,70 Remoxipride and raclopride are two other recently described members of this class. They are also selective D2 receptor blockers with preferential action in mesolimbic areas 71 and their clinical efficacy has been evaluated in several studies [72][73][74][75] in which they showed an antipsychotic efficacy comparable to that of traditional neuroleptics, demonstrating that the selective dopaminergic approach has consistently produced compounds that are currently employed in the clinical treatment of schizophrenia.…”
Section: Dopamine Depression and Schizophreniamentioning
confidence: 99%